The impact of high pressure on glucosinolate profile and myrosinase activity in seedlings from Brussels sprouts. (December 2016) - Wang, Jia; Barba, Francisco J.; Frandsen, Heidi B.; Sørensen, Susanne; Olsen, Karsten; Sørensen, Jens C.; Orlien, Vibeke
Abstract: The potential of high pressure (HP) to control bioactive components using seedlings of Brussels sprouts as a simple non-chopped vegetable system was examined. Enzyme activity in situ compared to purified enzyme and residual enzyme substrate in situ are used as three complementary measures for the HP effect. Purified myrosinase and seedlings of Brussels sprouts were submitted to HP 200–800 MPa at 5 °C for 3 min. The myrosinase activity decreased for both myrosinase systems upon increasing pressure to 800 MPa. Applying first-order kinetic to determine activation volumes revealed a linear relationship from 400 to 600 (ΔV # = − 19.04 mL/mol) and 450–600 MPa (ΔV # = − 37.79 mL/mol) for seedlings and purified myrosinase, respectively, indicating a protective effect of the plant matrix against enzyme inactivation. Purified myrosinase was activated at 200 MPa but at 800 MPa the glucosinolate degradation due to pressure induced disruption of the plant matrix seems to be partly counter-acted by myrosinase inactivation. Industrial relevance: High Pressure (HP) processing is an effective non-thermal preservation treatment for liquid and solid food. Moreover, over the last years, the potential of this technology to improve health and safety attributes of foods has been demonstrated. In particular, the ability of HP to preserve bioactive compounds has been established. There are only few studies evaluating the impact of HP on the complex bioactive glucosinolates-myrosinase. Therefore, this study opens the doors through the application of HP to preserve the bioactive glucosinolates in cruciferous vegetables by creating new processing solutions through controlled enzyme inactivation. Thus, HP could be an effective tool to achieve more effective solutions to obtain the new generation of convenient food and meet the need for new bioactive food products. Highlights: Purified myrosinase and seedlings of Brussels sprouts submitted to high pressure (HP) Linear relationship for seedlings and purified myrosinase at 400–600 MPa Purified myrosinase was activated at 200 MPa Myrosinase activity from seedlings decreased upon increasing pressure to 800 MPa Maximum degradation of glucosinolates in pressurized seedlings after HP at 600 MPa